2022
DOI: 10.1029/2022gl099586
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Configuration Relationship Between the Morphological Characteristics of Lightning Channels and the Charge Structure Based on the Localization of VHF Radiation Sources

Abstract: The spatial distribution of charge plays a crucial role during lightning development (Iudin et al., 2017;Zheng et al., 2019). A typical thunderstorm cloud has a three-layer charge structure: a positive charge region at the top, a negative charge region in the middle and a small positive charge region at the bottom (Krehbiel, 1986;Williams et al., 1985). At present, the vertical layered structure is mainly used in research to reveal the propagation behavior of lightning (Krehbiel, 2003;Nag & Rakov, 2009;Qie, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Li et al. (2022) indicated that the morphology of the lightning channel (bifurcation and turning) could reflect the charge structure of thunderstorms, and in this paper, we further used the morphology of the lightning channel as a bridge to build a connection between thunderstorm electricity and thunderstorm dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Li et al. (2022) indicated that the morphology of the lightning channel (bifurcation and turning) could reflect the charge structure of thunderstorms, and in this paper, we further used the morphology of the lightning channel as a bridge to build a connection between thunderstorm electricity and thunderstorm dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…The geometry of lightning is fractal (Riousset et al., 2007; Vecchi et al., 1994), and the FD can characterize the complexity of lightning channels and quantitatively describe the morphology of lightning channels (Li et al., 2022). The box‐counting method was used to calculate the FD of each lightning (see Maragos and Fan‐Kon (1993) for details) with the following formula: FD=limεtrue→0log0.25emN(ε)log1ε $\text{FD}=\underset{\varepsilon \to 0}{\mathrm{lim}}\frac{\log \,N(\varepsilon )}{\log \frac{1}{\varepsilon }}$ where FD is the fractal dimension, ε is the edge length of the box, and N is the number of boxes covered.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations